The Application of NdFeB in the Magnetic Force Actuator - DONG Enyuan; YIN Guangxiao; WANG Yongxing; DUAN Xiongying; ZOU Jiyan (Institute of Advanced Engineering and Science, 2012)
In this paper, NdFeB is used to design a new type of magnetic force actuator (MFA) with simple structure and high reliability. The permanent magnets are fixed on the static iron-core to generate a magnetic field, while the movable part locates within the magnetic field. It can drive the arc extinguishing unit powered by the Lorentz force, and this can be applied to the operation of the long-stroke high voltage circuit breaker (HVCB). At the open and closed position, the PMs generate holding force for the moving iron-core to keep the static state. Then, the finite element method(FEM) and prototype test are adopted to study the properties of PM and characteristics of the actuator. The simulation concludes that the material type and structure size of PM, end cap material and processing deviation of the actuator will impact the static characteristic of the actuator. The results of the test on prototype show that MFA using NdFeB can achieve the high power output, which is conductive for electronic control as well as the displacement tracking. Due to its stable performance, NdFeB is reliable in the running of the magnetic force actuator. DOI: http://dx.doi.org/10.11591/telkomnika.v10i6.1410